Kinetics and isotherms of asphaltene adsorption in narrow pores. (August 2016) - Alkafeef, Saad F.; Al-Marri, Salem S.
Abstract: New data relating to the kinetics and adsorption isotherms of asphaltene in consolidated sandstone core samples are reported. The data were obtained from the measurements of electrokinetics of consolidated sandstone core samples in asphaltene/toluene solutions and petroleum oils. The numerical reduction in the (negative) zeta potential of the sandstone samples were attributed to the adsorption of positively charged molecules of asphaltenes. The hydrodynamics thickness δ of adsorption of asphaltene were followed by monitoring the pressure increase that occurred as the adsorbed layer restricted the rock pores and applying Poiseuille's equation. The flow rates indicated a plateau of asphaltene adsorption at a pore blocking thickness of about δ / r = 0.3, which was also the point at which the streaming current reached a plateau. After increasing to about 30% of the pore radius, the adsorbed layer thickness δ stopped growing either with time or with concentration of asphaltene in the flowing liquid. Alternative hypotheses involving asphaltene adsorption isotherms have been investigated. A theoretical treatment advanced describing particle adsorption in the same terms as molecular adsorption and the Langmuir isotherm, with the free energy of asphaltene adsorption on the rock surface (modeled on silica) calculated on the basis of van der Waals attraction. Acceptable agreement was obtained with the electrokinetic measurements. Graphical abstract: Highlights: New data relating to the kinetics and adsorption isotherms of asphaltene in consolidated sandstone core samples are reported. Electrokinetic potential of sandstone samples under the adsorption of asphaltentic oil flow are discussed. The hydrodynamic thickness of adsorbed asphaltene layers into the narrow pores of sandstone rocks are discussed. Theoretical treatment of asphaltene adsorption in sandstone narrow pores is addressed.